Application of the essential oil extracting from leaves of plectranthus amboinicus L. for preserving cucumis melo L. after harvesting - Nguyen , Hoàng Thảo Ly; Le , Sĩ Ngọc; Pham , Thị Hà Vân; Nguyen , Thị Hiếu Trang (Journal of Technical Education Science, 2016)
In this research, the authors have evaluated the antifungal ability of Plectranthus amboinicus essential oil to three strains including Fusarium sp., Geotrichum sp. and Rhizopus sp. that causing cantaloupe’s spoilage after harvesting. Antifungus activities of P. amboinicus essential oil at concentration of 0,03% for Fusarium sp. were 93,187%, Geotrichum sp were 80,903%, and Rhizopus sp. were 32,127%. Minimal inhibitory concentrations (MIC) of P. amboinicus oil on above strains were 0,020%, 0,035%, and 0,050%, respectively. The fomula including P. amboinicus oil (0,050%), tween 80 (0,1%), glycerol (0,85%), acid stearic (0,5%), chitosan (1%), and acid acetic (2%) did not only reduce the development of the spore total of yeasts, molds (2,8x101 CFU/g) but also extended storage time (28 days) when compared to the control sample (1.5x103 CFU/g, 14 days, respectively).